2013
DOI: 10.3109/10715762.2013.816420
|View full text |Cite
|
Sign up to set email alerts
|

Effective NET formation in neutrophils from individuals with G6PD Taiwan-Hakka is associated with enhanced NADP+biosynthesis

Abstract: In response to infection, neutrophils employ various strategies to defend against the invading microbes. One of such defense mechanisms is the formation of neutrophil extracellular traps (NETs). Recent studies suggest that reactive oxygen species is a signal critical to NET formation. This prompts us to examine whether neutrophils from individuals with glucose-6-phosphate dehydrogenase (G6PD) Taiwan-Hakka variant, which are prone to oxidative stress generation, have altered ability to form NET. We adopted an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
4
21
0
1
Order By: Relevance
“…To confirm that the classical macroautophagy machinery was not involved in the transport of vesicular NE to the nucleus, we assessed perinuclear co-localization of LC3B and NE in neutrophils isolated from HDs by confocal microscopy. As previously observed (Fig 2), NE translocated to the area around the nucleus 1h post-stimulation with PMA ( Fig In contrast, previous studies had suggested that PI3-kinase inhibition affects NETosis via compromising macroautophagy [3][4][5][6][7][8] . Most of these studies, however, did not analyse the effect of PI3-kinase inhibition on ROS production [4][5][6]8 .…”
Section: To the Editorsupporting
confidence: 81%
See 1 more Smart Citation
“…To confirm that the classical macroautophagy machinery was not involved in the transport of vesicular NE to the nucleus, we assessed perinuclear co-localization of LC3B and NE in neutrophils isolated from HDs by confocal microscopy. As previously observed (Fig 2), NE translocated to the area around the nucleus 1h post-stimulation with PMA ( Fig In contrast, previous studies had suggested that PI3-kinase inhibition affects NETosis via compromising macroautophagy [3][4][5][6][7][8] . Most of these studies, however, did not analyse the effect of PI3-kinase inhibition on ROS production [4][5][6]8 .…”
Section: To the Editorsupporting
confidence: 81%
“…In order to shed light on the poorly understood steps downstream of ROS, resulting in NETosis, several groups have recently explored macroautophagy [3][4][5][6][7][8] , a cellular degradation pathway for cytoplasmic constituent delivery to lysosomes, which reshapes membrane compartments and could, therefore, be involved in hydrolase access to the nucleus. However, in all of these studies no direct correlation of macroautophagic activity and NETosis could be reported, and only pharmacological inhibition of phosphatidylinositol-3 (PI3)-kinase activity was used to compromise macroautophagy.…”
Section: To the Editormentioning
confidence: 99%
“…For instance, G6PD-deficient granulocytes have an impaired ability to generate superoxide, nitric oxide and hydrogen peroxide [71]. On the other hand, G6PD-deficient neutrophils show increased superoxide and hydrogen peroxide production [72]. More studies are needed to solve such a riddle.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of ATP, ADP and AMP were determined using UPLC under conditions as previously described for measurement of nicotinamide nucleotides [41].…”
Section: Determination Of Adenine Nucleotidesmentioning
confidence: 99%